FOXM1 Inhibition Enhances the Therapeutic Outcome of Lung Cancer Immunotherapy by Modulating PD‐L1 Expression and Cell Proliferation - Hamadi Madhi; Jeon‐Soo Lee; Young Eun Choi; Yan Li; Myoung Hee Kim; Yongdoo Choi; Sung‐Ho Goh (Advanced Science, 2022)
Abstract Programmed death‐ligand 1 (PD‐L1) is a major target to cancer immunotherapy, and anti‐PD‐L1 and anti‐PD‐1 antibody‐mediated immunotherapy are being increasingly used. However, immune checkpoint inhibitors (ICIs) are ineffective in treating large tumors and cause various immune‐related adverse events in nontarget organs, including life‐threatening cardiotoxicity. Therefore, the development of new therapeutic strategies to overcome these limitations is crucial. The focus of this study is the forkhead box protein M1 (FOXM1), which is identified as a potential therapeutic target for cancer immunotherapy and is associated with the modulation of PD‐L1 expression. Selective small interfering RNA knockdown of FOXM1 or treatment with thiostrepton (TST) significantly reduces PD‐L1 expression in non‐small‐cell lung cancer (NSCLC) cells and inhibits proliferation. Chromatin immunoprecipitation‐PCR reveals that FOXM1 selectively upregulates PD‐L1 expression by binding directly to the PD‐L1 promoter. In vivo animal studies have shown that TST treatment significantly downregulates PD‐L1 expression in human NSCLC tumors, while greatly reducing tumor size without side effects on normal tissues. Combined treatment with TST and anti‐4‐1BB antibody in the LLC‐1 syngeneic tumor model induces synergistic therapeutic outcomes against immune resistant lung tumors as well as 2.72‐folds higher CD3+ T cells in tumor tissues compared to that in the anti‐4‐1BB antibody treatment group.